An Academic–Practice Partnership at the University of Washington School of Public Health: The Student Epidemic Action Leaders (SEAL) Team. (November 2018) - Simckes, Maayan; Melius, Beth; Hawkins, Vivian; Lindquist, Scott; Baseman, Janet
In 2015, the University of Washington School of Public Health, Department of Epidemiology established the Student Epidemic Action Leaders (SEAL) team to provide public health students with experience in field epidemiology in state and local public health communicable disease divisions. The University of Washington Department of Epidemiology developed the SEAL team in collaboration with the Washington State Department of Health to offer public health graduate students opportunities to contribute to the real-time needs of public health agencies during a communicable disease event and/or preparedness event. The SEAL team combines classroom and field-based training in public health practice and applied epidemiology. During the first 2 years of the SEAL team (2016-2018), 34 SEALs were placed at 4 agencies contributing more than 1300 hours of assistance on 24 public health projects.